KEDUDUKAN HUKUM SURAT PENGAKUAN HAK (SPH) ATAS TANAH SEBAGAI BUKTI AWAL PROSES PENDAFTARAN TANAH - Suhardi Suhardi (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2015)
Abstract : This thesis examines the legal standing of acknowledgement letter of right to land as a right base to process a land registration that it has purpose to review and analyze the aspect of legal standing of acknowledgement letter of right to land in a system of valid agrarian law, rather related to the publishing authority, arrangement of society, function in process of land registration, analysis of legal power of the acknowledgement letter of right to land in land dispute and powerof authentication in formal and material. By using a normative legal research can be put forward that it meets with the legal standing of the acknowledgement letter of right to land that one of right of bases in process of land registration (certification) and legal power of authentication of the acknowledgement letter of right to land in land dispute represents an under-hand proof and therefore in land dispute must be seen the other proof as witness, admission, suspicion and oath, sp that in material, the obtained truth is not only formal legal truth. On the basis, this research recommends, related to the legal standing and the power of authentication of the acknowledgement letter of right to land that the National of Agency (BPN) keeps on making the massive certification in order to it can be stepped up becoming certificate of right to landand in settlement of land dispute to give prority in way and mechanism to engage in deliberation by relying on mechanism of formal legal settlement. Keywords :      Acknowledgement letter of right to land, Under-hand Documents, Certificate of Proprietary Right